Evaluation of Resilient Modulus of Subgrade and Base Materials in Indiana and Its Implementation in MEPDG - Richard Ji; Nayyarzia Siddiki; Tommy Nantung; Daehyeon Kim (The Scientific World Journal)
In order to implement MEPDG hierarchical inputs for unbound and subgrade soil, a database containing subgrade MR, index properties, standard proctor, and laboratory MR for 140 undisturbed roadbed soil samples from six different districts in Indiana was created. The MR data were categorized in accordance with the AASHTO soil classifications and divided into several groups. Based on each group, this study develops statistical analysis and evaluation datasets to validate these models. Stress-based regression models were evaluated using a statistical tool (analysis of variance (ANOVA)) and Z-test, and pertinent material constants (k1, k2 and k3) were determined for different soil types. The reasonably good correlations of material constants along with MR with routine soil properties were established. Furthermore, FWD tests were conducted on several Indiana highways in different seasons, and laboratory resilient modulus tests were performed on the subgrade soils that were collected from the falling weight deflectometer (FWD) test sites. A comparison was made of the resilient moduli obtained from the laboratory resilient modulus tests with those from the FWD tests. Correlations between the laboratory resilient modulus and the FWD modulus were developed and are discussed in this paper.